GAMBARAN TINGKAT PENGETAHUAN KESEHATAN GIGI DAN MULUT PADA SANTRI PONDOK PESANTREN AL-MUAWANAH CIBIRU (Poltekkes Kemenkes Bandung, 2023)
Knowledge of oral health is an effort that is included in prevention to maintain dental and oral health. Lack of knowledge makes dental and oral health less attention and can lead to dental and oral health problems. A preliminary study conducted on 20 students of the Al-Muawanah boarding school, showed the results of the knowledge level of 5 students in the good knowledge category, 10 students in the sufficient knowledge category, and 5 students in the lack of knowledge criteria. Islamic boarding schools teach to live clean and healthy but have never received counseling about health, besides that there are no dental health workers making health, especially dental and oral health, not getting the attention of the students of Pondok Al-Muawanah itself. The purpose of the study was to describe the level of knowledge of dental and oral health of the students of Al-Muawanah Islamic Boarding School, Cibiru. This type of research is descriptive research. Data was collected through a questionnaire distributed online. The population in this study amounted to 127 people. The data is processed and presented in the form table a frequency distribution The results showed that the level of knowledge on the dental and oral health of the students of Al-Muawanah Islamic Boarding School, Cibiru was in the moderate level category of 21 students (65.6%) and knowledge of how to maintain oral health in the good category of 27 students (84.4%). The conclusion is that the level of knowledge of oral health on the students of Pondok Pesantren Al-Muawanah Cibiru is in the sufficient category, while the maintenance of dental and oral health is good.